Recent Progress of Cyanine Fluorophores for NIR‐II Sensing and Imaging - Zhou, Hui‐Jie; Ren, Tian‐Bing (Chemistry, an Asian journal, 2022)
The cyanine fluorophores, a kind of classic organic fluorophores, are famous for their high extinction coefficient, simple synthetic route, and relatively long absorption and emission wavelengths. Moreover, the excellent biocompatibility and low toxicity in biological samples make cyanine fluorophores show excellent application value in the biomedical field, especially in Near‐Infrared II (NIR‐II) sensing and imaging. In this review, we briefly outline the history, characteristics, and current state of development of cyanine fluorophores. In particular, we described the application of cyanine fluorophores in NIR‐II sensing and imaging. We hope this review can help researchers grab the latest information in the fast‐growing field of cyanine fluorophores for NIR‐II sensing and imaging. Cyanine dye‐based NIR‐II fluorescent probes, owing to their high extinction coefficient and simple synthetic procedure, are highly useful for deep‐tissue high‐contrast imaging in vivo. In this review, we briefly outlined the history of the cyanine, summarized the chemical structures of recently developed NIR‐II cyanine dyes, and highlighted their biomedical applications in NIR‐II sensing and imaging.